The Effect of Recruitment and Career Development on The Spirit of Teachers’ Work Performance in MTs Nurul Huda - Lestari, Bela; Novitasari, Dewiana; Silitonga, Nelson; Asbari, Masduki (AGUSPATI Research Institute, 2020)
The objectives in this study are: (1) Want to know the effect of recruitment on morale teachers at MTs Nurul Huda, (2) Want to know the influence of career development on the spirit of work teachers at MTs Nurul Huda, (3) Want to know that recruitment and career development have an effect on the spirit of teacher work at MTs Nurul Huda. The method used in this study is quantitative in nature associative descriptive. In this study, the saturated sampling method is a technique of determining when all members of the population are used as samples. The samples used in this study are all teachers at MTs Nurl Huda are 25 people. Data collection methods with questionnaires (polls) that have tested validity and reality. The data analysis techniques that have been used are tests correlation, coefficient determination test, regression test and hypothesis test using SPSS 18.0 program. Results this research shows that Recruitment (X1) and Career Development (X2) have an effect on employee productivity (Y) of 81.3% while the remaining 18.7% is affected by variable otherwise un scrutinized. The results of regression and career development analysis of the spirit of work are obtained 4581 + -(6,375) X1 + 6,992 X2. This constant of 4,581 means that if there is an increase in the value of the variable motivation and work environment, employee work productivity is 4,581%. Based on hypothesis test F recruitment and career development against the spirit of teachers obtained results F count>F table =47.933>3.44. It states that it has a significant influence on the recruitment and development of career towards the spirit of teacher work at MTs Nurul Huda. The conclusions of this study are recruitment and career development has a significant impact on the spirit of work. In this study the authors advice and input to the school leadership of MTs Nurul Huda, namely the need for school policy in improving recruitment, career development and work spirit significantly.